(The Prospect of Derivated Fennel Oil (Foeniculum vulgare Mill) Development in Indonesia) - M Maman Rohaman; Sumarsi -; Eddy Sapto Hartanto (Balai Besar Industri Agro, 2005)
Fannel (Foeniculum Vulgare Mill) has been well known by indonesia people. Fannel seeds have strong pleasant odour because of essential oil. The major essential oil constituents of fannel were anethole and limonene, with more than 80% of the total oil. The other chemical consituents were- pinene, myrcene, y-terpinene, fenchone, estragole and fenchyl acetate. To increase the use of fannel oil, anethole consituent can be converted to its derivations by oxydation, acetylation, reduction, esterification and alcylation processes. Fennel seeds are used as a flavoring for goods and beverages and the essential oil from seed and plant has flavoring, cosmetic and pharmacuetical uses. The tendency in consumming medicine from natural plant material source, cause in the increasing use fennel as medicine raw material, especially the simplified usage which was used in traditional medicine.